Increasing Knowledge and Promoting Better Attitude towards Appropriate Self-Medication in Sungai Ambawang Community through CBIA - eka kartika untari; Robiyanto Robiyanto; Pratiwi Apridamayanti; Muhammad Akib Yuswar; Rafika Sari; Nera Umilia Purwanti; Ressi Susanti (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
Self-medication practice in the community tends to increase. One of the factors that influence this trend is the variation of non-prescription drugs and advertisements. Although in self-medication people are allowed to determine their own medication, but it has the potential to create problems. Sungai Ambawang Sub-district is one of the trans Kalimantan; accordingly the medicine products from outside West Kalimantan can be transported through this area. This community service activity (PKM) aimed to increase knowledge and encourage positive attitudes, so that their behavior of self-medication becomes appropriate. This PKM was carried out by the method of communitybased interactive approach (CBIA) in 2 steps. This activity involved 66 community health center cadres. The participants’ knowledge and attitude were measured twice (pretest and posttest) through questionnaires, then analyzed descriptively and statistically using the Wilcoxon test. The observations showed that most of the participants had bought medicines without a prescription for self-medication (78.7%), obtained the medicine from pharmacies (65.2%), purchased medicines over the counter (45.4%), and frequently used analgesic-antipyretics (77%). The results of the Wilcoxon test showed that there were significant differences between knowledge and attitudes before and after CBIA intervention. Based on the results of this intervention, it was concluded that the CBIA intervention done as the PKM activity could increase knowledge and encourage positive attitudes regarding appropriate self-medication practices.